THE PURSUIT OF TRUTH IN THE CONTEXT OF POST-COLONIAL SRI LANKAN CONFLICTS THROUGH MICHAEL ONDAATJE’S ANIL’S GHOST AND GUNADASA AMARASEKARA’S ASATHYA KATHAWAK - Jayasinghe, Manouri K. (International Journal of Research -GRANTHAALAYAH, 2022)
Sri Lankan history is fraught with numerous attempts of invasion and colonization from time immemorial. The European occupation being the major one, it lasted for 443 years until 1948. The post-independence period revealed the strong influence of colonization on the socio-economic, religious, and cultural mindset of the colonized. The policy of ‘divide and rule’ implemented by the Europeans paved the way for political conflicts among ethnic groups. The youth of both the Sinhala and Tamil ethnic factions of the population opposed the political decisions of the then Sri Lankan governments at different periods of time and this led to the Sinhala youth insurrection and the 30-year liberation war by Tamil separatist guerillas. Ondaatje in Anil’s Ghost and Amarasekara in Asathya Kathawak have recognized these conflicts and their outcome through literature. The protagonists of these novels are eager to discover the truth and the perpetrators of violence during the uprisings in order to mete out justice to the memory of the victims. The different narrative techniques used, help in understanding the storyline through which the truth concerning the criminal occurrences of the era are uncovered.